Cavity-nesting bee communities in areas with different levels of vegetation disturbance. (3rd May 2020) - Lourenço, Anete P.; Santos, Ana Paula M.; Checon, Hélio H.; Costa, Mayra R.; Assis Júnior, Sebastião L.
ABSTRACT: The reasons for the decline of bee diversity and abundance include the destruction and loss of natural habitats. Protected areas are created for biodiversity conservation, but these areas vary strongly in their level of vegetation disturbance. Using trap-nests, we assessed changes in solitary bee abundance, richness, and composition in areas ranging from naturally conserved to degraded. Solitary bees were sampled during an 18-month period in three areas of southeastern Brazil: a preserved area in Rio Preto State Park – PERP; a restored/altered area with exotic plants at the Federal University of the Jequitinhonha and Mucuri Valleys – JK Campus; and a degraded area in Biribiri State Park – PEBi. A total of seven species of bees built 115 nests. In the degraded area, only two nests were built. Abundance of built nests was higher in the preserved area (PERP), but diversity was higher in the restored area (JK Campus). Our results show that the solitary bee population responds positively to habitat complexity (local scale). The presence of a diverse solitary bee fauna in the restored area indicates that altered areas should also be protected as suitable areas for re-colonization of cavity-nesting bees.